Amelioration of interfacial properties for CGF/PA6 composites fabricated by ultrasound-assisted FDM 3D printing. (April 2023) - Zhang, Run; Yu, Liguo; Chen, Ke; Xue, Ping; Jia, Mingyin; Hua, Zetian
Abstract: Perfect interfacial adhesion is difficult to be achieved for hot-melt continuous glass fiber (CGF)/PA6 prepregs, which dilutes various physicochemical properties of samples by fused deposition modeling (FDM) technology. Herein, an innovative FDM 3D printing device with ultrasonic embedding is designed, and the influence of ultrasonic frequency on the interfacial adhesion is investigated. The introduction of ultrasound effectively enhances the interfacial adhesion between CGF and PA6, improving bonding strength not only between interlayers but also among inter-filaments. In addition, the porosity of printed samples significantly decreases from 4.52% to 1.33% with the increased ultrasonic frequency, and the mechanical properties are all ameliorated. This study provides a practical and efficient approach to solve the interface bonding problem of FDM 3D printing continuous fibers reinforced polymer samples. Graphical abstract: Image 1 Highlights: An innovative FDM 3D printing device with ultrasonic embedding. A practical and efficient approach to solve interface adhesion of CGF and PA6. Porosity of FDM 3D printing samples significantly decreases. Interlaminar shear strength of samples is increased by more than 100%.